2020
DOI: 10.1108/jrit-09-2019-0068
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation fundamentals: redesigning an online course using adult learning principles and trifecta of student engagement framework

Abstract: PurposeThe purpose was to describe the redesigning of an online course that utilized adult learning principles and a framework to engage students.Design/methodology/approachThe methodology used is a first person account from the instructor point of view.FindingsFindings indicate that the teaching strategies used encouraged student engagement in the course.Research limitations/implicationsThe research is limited to one course with less than 20 students.Practical implicationsOther online instructors can utilize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Occasionally, group members may need to change groups, so the instructor could facilitate changing the groups and help them adjust to different groups, and revisit the group contract. Regarding the size of the groups, this study found that a group of three works well, which aligns with prior studies that 3–6 students for group projects are appropriate (Culen et al, 2014 ; Leslie, 2020 ; Urquiza-Fuentes & Paredes-Velasco, 2017 ). It may be even more important in online courses to keep the group size relatively small, given that students need to navigate out-of-class tasks and time.…”
Section: Discussionsupporting
confidence: 89%
“…Occasionally, group members may need to change groups, so the instructor could facilitate changing the groups and help them adjust to different groups, and revisit the group contract. Regarding the size of the groups, this study found that a group of three works well, which aligns with prior studies that 3–6 students for group projects are appropriate (Culen et al, 2014 ; Leslie, 2020 ; Urquiza-Fuentes & Paredes-Velasco, 2017 ). It may be even more important in online courses to keep the group size relatively small, given that students need to navigate out-of-class tasks and time.…”
Section: Discussionsupporting
confidence: 89%
“…The learning strategies applied by the lecturers will influence the students' enthusiasm, including in the online lectures [8]. Previous findings show the effectiveness of online learning with face-to-face meetings.…”
Section: Introductionmentioning
confidence: 94%
“…This is mostly to be noted in the COVID 19 academic environment, that most lecturers were forced to go online by the pandemic and the level of experience with digital tools was basic, let alone having to redesign courses. Leslie (2021) argues that a redesigned course is more effective and important for encouraging engagement.…”
Section: Literature Reviewmentioning
confidence: 99%